GE_GERICHTE P/23028/2021 vom 8. August 2022 - GE Cour de justice (2022)
ORDONNANCE DE CLASSEMENT;DIFFAMATION;MENACE(DROIT PÉNAL);CONTRAINTE(DROIT PÉNAL);DROIT D'ÊTRE ENTENDU;MOTIVATION | CPP.319; CP.177; CP.180; CP.181; Cst.29